Mental health symptoms of youth initiating psychiatric care at different phases of the COVID-19 pandemic - Brent R. Crandal; Andrea L. Hazen; Kelsey S. Dickson; Chia-Yu Kathryn Tsai; Emily Velazquez Trask; Gregory A. Aarons (BMC, 2022)
Abstract Objective To examine differences in caregiver and youth reported mental health symptoms for youth initiating mental health treatment through phases of the Coronavirus Disease (COVID-19) pandemic, compared with symptomology reported the prior year. Study design This retrospective study analyzes group differences in mental health symptoms (Pediatric Symptom Checklist; PSC-35) based on 7874 youth seeking treatment in publicly funded mental health treatment programs during California's Stay-At-Home order (March-May, 2020) and the prolonged pandemic (May-December, 2020) phases of the COVID-19 pandemic as compared with matching groups in 2019. Results Youth entering mental health treatment services, and their caregivers, reported significantly increased internalizing, externalizing, and attention-related symptoms during the prolonged pandemic phase, but not during the acute stay-at-home phase of the COVID-19 pandemic, and with small effect sizes. Group comparison analyses did not detect a significantly larger effect for Sexual and Gender Diverse (SGD) youth who identify as lesbian, gay, bisexual, asexual, transgender, Two-Spirit, queer, and/or intersex, and Black, Indigenous, People of Color (BIPOC). Conclusions A large-scale comparison of youth mental health symptoms before and during the COVID-19 pandemic suggests that mental health was disrupted for youth seeking treatment as the pandemic prolonged throughout 2020.